Socio-economic analysis of riverine flooding on low-income dwellings: Adayar River, a case study - Saravanan, Suriva; Basavaraj, Mudgal; Nelliyat, Prakash (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Flood damage assessment plays a vital role in providing information to policy developers. Nowadays, due to urbanization, the impact of flooding on communities is extensive, including tangible damage to property, the environment, and infrastructure as well as intangible damage due to stress, health hazards, and hardship. This paper provides an overview of a detailed flood assessment study conducted in the Kotturpuram Housing board area, located on the flood plain of the Adayar River in Chennai, India. A relatively simple approach to data collection was adopted, being a Questionnaire Survey (QS) as well as semi-structured interviews and observation techniques, due to data and research limitations.
Keywords: Adayar river; socio-economic analysis; flood damage; stage-damage curve; TIN